Straphanger : saving our cities and ourselves from the automobile - Grescoe, Taras (Times Books, 2012)
"The perception of public transportation in America is often unflattering--a squalid last resort for those with one too many drunk-driving charges, too poor to afford insurance, or too decrepit to get behind the wheel of a car. Indeed, a century of auto-centric culture and city planning has left most of the country with public transportation that is underfunded, ill maintained, and ill conceived. But as the demand for petroleum is fast outpacing the world's supply, a revolution in transportation is under way."--